(untitled) (Research, Society and Development, 2021)
Mushrooms of the genus Pleurotus are cultivated as food, for medicinal purposes and also because they are sources of enzymes of industrial interest. The present study aimed to evaluate mycelial growth and verify the activity of P. djamor proteases. This mushroom was grown on potato dextrose agar (BDA) with yeast extract (YE) 0.5% (w/v). In order to evaluate the speed of radial mycelial growth (VCR) and mycelial density, P. djamor was grown in five media with 0.5% YE (w/v): potato dextrose agar (BDA+YE), Sabouraud agar (SAB + YE), malt extract agar (MEA+YE), purple yam agar (PYA+YE) and cará-de-espinho agar (SYA+YE). Proteolytic activity was determined by the agar block method. For the vertical mycelial growth evaluation (VCM), cupuaçu (CE) and pineapple (PE), açaí seed (AS) and sawdust (SAW) exocarps were used, supplemented with rice bran (RB) or wheat bran (WB). Significant VCR was observed in SYA+YE (11.26 mm / day) and PYA+YE (10.97 mm / day). However, SAB+YE favored mycelial density, so it was the medium selected for obtaining inoculum for the tests to evaluate mycelial growth of P. djamor in lignocellulosic residues. Significant proteolytic activity was determined in BDA+YE (17.7 mm), MEA+YE (17.6 mm) and SAB+YE (17.0 mm). Strong mycelial density and significant CMV was determined in CE+WB (0.37 cm / day) and CE+RB (0.30 cm / day). Rainforest substrates are efficient for mycelial cultivation and protease production by P. djamor.